Pengaruh Pelayanan Prima Terhadap Kepuasan Konsumen Pada Koperasi Suka Maju Kabupaten Probolinggo. - Vikawati Windra Rini; Agustina Pujiastuti (Ecobuss, 2017)
This study was conducted at the Cooperative Suka Maju Probolinggo based on the results of the initial survey showed to gain the trust of consumers, the Cooperative Suka Maju continue to show a perfect impression on the consumer to continue to improve the quality of service and continue to pay attention to ethics in the delivery of services in order to achieve consumer satisfaction. The purpose of this study was to determine the form factor of excellent service attitude, attention and action simultaneously and partially on customer satisfaction in the Cooperative Suka Maju, and know the most dominant factor between attitude, attention, and action on Consumer Satisfaction In Love Forward Cooperative. This type of research is classified as causal research, the variables used include excellent service with attitude, attention, and action as well as customer satisfaction. The method used to analyze the research data that is using the quantitative descriptive approach in the form of multiple regression analysis and determination because it is concerned with the calculation to answer the problem formulation and testing of hypotheses proposed use statistics. The results showed that consumers are satisfied with the excellent service at the Cooperative Suka Maju because to the provision of services in accordance with customer expectations based on the principle of 3A is Attitude, Attention, Action. Customer satisfaction by 59% influenced by such excellent service attitude, attention, and action while the remaining 41% of the amount of consumer satisfaction is influenced by other Keywords: consumer satisfaction, excellent service attitude, attention, and action